Vernalization requirement of winter bread wheat modern varieties (Tritikum aestivum L.) - Н. В. Булавка; Л. М. Голик (Plant Varieties Studying and Protection)
The study of vernalization requierement of winter bread wheat 87 modem varieties from Ukraine and Russia showed significant domination - 81.6% - of varieties with short vernalization requierement (30-40 days). Vernalization requierement differences among varieties from different climatic zones were revealed.